Biomass Burning is an Important Source of Organic Aerosols in Interior Alaska. Issue 12 (23rd June 2021) - Haque, Md. Mozammel; Kawamura, Kimitaka; Deshmukh, Dhananjay K.; Kunwar, Bhagawati; Kim, Yongwon
Abstract: Biomass burning (BB) affects air quality, the global cycling of carbon, climate, and human health. Intensive BB activities occur throughout the year due to wildfires and domestic wood burning in Fairbanks. We collected total suspended particle samples from the air in Fairbanks from June 2008 to June 2009. Here, we report seasonal variations in the molecular composition of organic aerosols and its BB contributions in Fairbanks. Levoglucosan is the dominant BB tracer (annual mean 67 ± 77 ng m −3 ), showing a winter maximum (145 ± 47 ng m −3 ) and spring minimum (12 ± 12 ng m −3 ). Levoglucosan showed significant correlations ( p  < 0.001) with organic carbon (OC), water‐soluble organic carbon (WSOC), and PM2.5, indicating a significant contribution of BB to hazes in Fairbanks. However, no correlation exists between levoglucosan and non‐sea salt potassium (nss‐K + ), which has been proposed as a BB tracer. We hypothesize that nss‐K + is removed by deposition on the inner surfaces of woodstove chimneys. Levoglucosan contributes 3.6% to OC and 6.3% to WSOC in winter, indicating that BB significantly affects carbonaceous aerosols in central Alaska. Moreover, positive matrix factorization analysis demonstrates that BB is an important source (47.5%) of Fairbanks year‐round aerosols. We conclude that domestic wood burning is an important source of atmospheric particles that impact the air quality of Fairbanks, especially in winter. We presumed that Fairbanks BB products might be transported to the remote Arctic, potentially affecting the chemical composition of Arctic aerosols. These findings will be useful to better understand the seasonal influence of BB on the Arctic and subarctic aerosols. Key Points: Biomass burning (BB) emissions significantly contribute to carbonaceous aerosols and particulate matters in the central Alaska atmosphere Possible deposition of non‐sea salt potassium (nss‐K + ) on the inner surface of woodstove chimneys may cause an underestimation of nss‐K + in the Fairbanks aerosols Alaskan BB pollutants might be transported to the remote Arctic, which can affect the chemical compositions of Arctic aerosols